The enabling environment for large-scale food fortification in Madagascar - Resnick, Danielle (International Food Policy Research Institute, 2024)
Why is there high variability—both across countries and across different food staples—in the adoption and implementation of large-scale food fortification (LSFF)? A systematic diagnostic of the enabling environment for LSFF can identify key bottlenecks and help to calibrate policy interventions appropriately. This paper delineates the components of such a tool by focusing on two core elements of the enabling environment—political will and implementation capacity—and applies the framework to Madagascar. With more than 75 percent of its population living below the poverty line and almost 40 percent of children under five who are stunted, Madagascar faces major hurdles to addressing malnutrition, including weak consumer purchasing power, recurrent political crises, and frequent climate shocks that undermine agricultural productivity. LSFF has been identified in several national nutrition plans as an option for addressing malnutrition. Yet, thus far, only salt has been fortified at a national scale.